Robot telecontrolado para mejorar el monitoreo de mamíferos en bosques amazónicos - Condori Mamani, Miquias Edwin (2020)
This research presents the results of the design, construction and validation of a remote-controlled robotic device that aimed to improve the monitoring and inventory processes of larger mammals in the Amazon forests. The trial and error method was used for the construction and validation of the telecontrolled robot, using observation techniques for the recording of the results at the end of the tests, which were carried out at the "Quistococha" Tourist Resort. The results obtained demonstrate the advantage of using a robot with respect to humans in contexts that involve a risk to life, indicating that the robot reached 98% of records satisfactorily, and the costs of its use is evidently more economical in comparison to traditional monitoring (generally carried out by a group of people). And it is concluded that, with the creation and validation of the robot, the monitoring of mammals can be improved, since its use favours the increase in the number of records, allows the generation of a greater volume of data from the records, reaches a better average of displacement even in dangerous or inaccessible spaces, and has an economic cost.